MENELAAH KORELASI KISAH NABI YUSUF DENGAN TATA KELOLA KEUANGAN : KAJIAN QASHASH AL-QUR’AN - Maggu, Istiqamah; Muhammad Yahya; Hasyim Haddade (Jurnal Ilmiah Akuntansi Peradaban, 2025)
This study aims to examine the story of the Prophet Yusuf (AS) in the Qasas al-Qur'an as a source of values ​​for the development of financial governance from an Islamic perspective. The method used is a literature study of journal articles discussing public financial management, sharia accounting, risk management, and Qur'anic studies related to the story of the Prophet Yusuf (AS). The results of the study indicate that the strategy of seven years of abundance and seven years of famine reflects financial governance practices that emphasize long-term planning, resource control, risk mitigation, and public accountability. The values ​​of trustworthiness, prudence, and orientation towards the welfare of the people are the main principles in the management of public resources. These findings confirm the relevance of the story of the Prophet Yusuf (AS) as a normative foundation for financial governance. Keyword: Governance, Finance, Prophet Yusuf As